The maverick's Christmas kiss - Sims, Joanna (Love story writer) (Montana mavericks., 2024)
Dawson John is ranching royalty in Bronco and can usually get a date with any woman he wants. Music teacher Marisa Sanchez is a lot like the holidays—bright, full of cheer—so it’s no wonder the well-heeled cowboy is attracted to her. Marisa, though, insists they are too different for anything deeper than flirtation. Once the lights fade on the Mistletoe Pageant, she’ll be heading home to “real life” in blue-collar Tenacity